Tissue-specific sex difference in the metabolism of fatty acid esters of hydroxy fatty acids - Riecan, Martin; Domanska, Veronika; Lupu, Cristina; Patel, Maulin; Vondrackova, Michaela; Rossmeisl, Martin; Saghatelian, Alan; Lupu, Florea; Kuda, Ondrej (bioRxiv, 2023)
Fatty acid esters of hydroxy fatty acids (FAHFAs) are endogenous bioactive lipids known for their anti-inflammatory and anti-diabetic properties. Despite their therapeutic potential, little is known about the sex-specific variations in FAHFA metabolism. This study investigated the role of Androgen Dependent TFPI Regulating Protein (ADTRP), a FAHFA hydrolase. Additionally, tissue-specific differences in FAHFA levels, focusing on the perigonadal white adipose tissue (pgWAT), subcutaneous white adipose tissue (scWAT), brown adipose tissue (BAT), plasma, and liver, were evaluated using metabolomics and lipidomics. We found that female mice exhibited higher FAHFA levels in pgWAT, scWAT, and BAT compared to males. FAHFA levels were inversely related to Adtrp mRNA, which showed significantly lower expression in females compared with males in pgWAT and scWAT. However, no significant differences between the sexes were observed in plasma and liver FAHFA levels. Adtrp deletion had minimal impact on both sexes' metabolome and lipidome of pgWAT. However, we discovered higher endogenous levels of triacylglycerol estolides containing FAHFAs, a FAHFA metabolic reservoir, in the pgWAT of female mice. These findings suggest that sex-dependent differences in FAHFA levels occur primarily in specific WAT depots and may modulate local insulin sensitivity in adipocytes. However, further investigations are warranted to fully comprehend the underlying mechanisms and implications of sex effects on FAHFA metabolism in humans.
Keywords: FAHFA; male; female; adipose tissue; lipokines; Adtrp